Hydrophilic graphite oxide granular material prepared by electrochemical method and application thereof
The preparation of hydrophilic graphite oxide particle materials of different sizes through electrochemical method solves the problem of difficulty in controlling the size distribution of traditional graphite oxide particle materials, and realizes efficient removal of water pollutants and precious metal recovery, reducing preparation costs and simplifying Process flow.
Patent Information
- Application Number
- CN202411360862.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-09-27
AI Technical Summary
The existing graphite oxide particle materials have difficulty in controlling the size distribution during the preparation process, which affects the performance and application effect of the material, and the preparation process is high and there is a risk of environmental pollution.
The hydrophilic graphite oxide particle materials are prepared by electrochemical method, and the preparation of particles of different sizes is achieved by controlling the electrolyte composition and voltage, and the particle size and distribution are further controlled through filtration and centrifugal separation technology.
It realizes efficient removal of pollutants in water bodies and recycling of precious metal ions, reduces preparation costs, simplifies the process flow, and has environmentally friendly processes and no secondary pollution.
Smart Images

Figure CN119433552A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of environmental chemistry, and in particular, to a hydrophilic graphite oxide granular material prepared by an electrochemical method and an application thereof, in particular to a hydrophilic graphite oxide granular material with reducibility and a preparation method and application thereof, in particular to a preparation method of hydrophilic graphite oxide granular material of different sizes and an application thereof in terms of the recovery of pollutants and valuable precious metals in environmental water bodies. Background Art
[0002] Water pollution is becoming increasingly serious, posing a serious threat to the ecological environment and human health. Various organic pollutants, heavy metal ions and other harmful substances are discharged into water bodies in large quantities, causing great damage to water resources. How to efficiently remove pollutants from water bodies has become one of the hot issues in the field of environmental chemistry research.
[0003] Graphite oxide is a graphite derivative containing a large number of oxygen-containing functional groups, mainly including carboxyl, hydroxyl, epoxy, etc. The presence of these functional groups makes it have excellent hydrophilicity and chemical activity; graphite oxide has a large specific surface area and rich pore structure, which makes it have good adsorption capacity for pollutants in water; graphite oxide materials have good chemical stability and mechanical strength, and can maintain their structure and performance in complex water environments; in addition, graphite oxide materials also have good dispersibility, can be evenly distributed in water bodies, and fully contact with pollutants, thereby improving the treatment effect. Although the raw materials of graphite oxide are cheap, its preparation process (such as chemical oxidation, ultrasonic stripping, etc.) requires a large amount of chemical reagents and energy, resulting in a high overall preparation cost. Moreover, in the preparation process, how to accurately control the size distribution of graphite oxide particles is still a challenge, which may affect the performance and application effect of the material. Therefore, the development of a green preparation method for hydrophilic graphite oxide particle materials of different sizes is expected to play a greater role in the field of environmental protection, reduce the cost of material preparation, simplify related process flows, and provide greener technical support for solving water pollution problems.
[0004] Graphite oxide materials have a wide range of applications in many fields, such as water treatment, electrochemical sensors, energy storage, composite materials, medical and biotechnology infrared environmental remediation, etc. We designed and synthesized an electrochemical oxidation method to prepare hydrophilic graphite particles of different sizes, and applied it to the environmental water remediation process, effectively achieving the removal of target pollutants and the recovery of precious metal ions in environmental water. Summary of the invention
[0005] In view of the defects in the prior art, the purpose of the present invention is to provide a hydrophilic graphite oxide particle material prepared by an electrochemical method and its application, so as to solve the problem of difficulty in controlling the size distribution of graphite oxide particles in traditional technology.
[0006] The electrolyte of the present invention is water, conventional acid-base solution or small molecule inorganic salt solution (single component, no additional organic matter added, no strong oxidizing property, ions do not have intercalation effect), and only weak conductivity is guaranteed at extremely low solubility (pH=1-12 or not more than 5mmol / L). At the same time, at a relatively high electrolysis voltage (25-60V) and a suitable electrode spacing, it is ensured that the current acts on the surface of the graphite anode (high voltage, low conductivity), random electrons interrupt the CC bond (CC fracture near the particles), resulting in the graphite surface falling off in particles and irregular peeling.
[0007] If high concentrations or other ions (such as nitrate) are used with intercalation effects, they will be intercalated between graphite layers during electrolysis, achieving exfoliation, and obtaining layered graphene (without surface defects) instead of graphite particles.
[0008] The electrolyte used in the present invention has simple components and low solubility. The current on the electrode can only act on the electrode graphite. Under a relatively high voltage (25-60V), the surface graphite structure is destroyed, carbon defect sites are created, and electrons are stored, so that it has reducing properties. The graphite plate after the reaction is honeycomb-shaped. That is, the present invention can make the current act on the surface of the anode graphite to produce a destructive effect, irregularly interrupt CC, and fall off graphite particles (non-graphite flakes, graphene), and the surface of the graphite particles carries electrons, which has the characteristics of reducing properties and can be used for heavy metal wastewater treatment, reducing heavy metal ions and recycling. The material can directly realize the reduction of metal ions without the need for additional reagents, pH adjustment, or application of temperature and other conditions. The material has a rich carbon defect structure and a certain amount of movable electrons (graphene is a complete peeling of the entire layer, and there are no carbon defects), which is used to realize the direct reduction of metal ions. The hydrophilicity is highly dispersed in an aqueous environment (1-3000mg·L -1 ).
[0009] The object of the present invention is achieved through the following solutions:
[0010] In a first aspect, the present invention provides a hydrophilic graphite oxide particle material prepared by an electrochemical method, which is prepared by the following method:
[0011] S1. Select graphite as the anode, insert the anode and cathode into the electrolyte, and perform electrolysis (electrochemical oxidation) at a constant potential;
[0012] S2. After the electrolysis is completed, the obtained electrolytic solution is filtered, and the filtrate is centrifuged to obtain the hydrophilic graphite oxide particle material.
[0013] As an embodiment of the present invention, in step S1, the cathode used for electrolysis is graphite. The graphite material is used as an electrode and is treated as follows before use: the surface of the purchased graphite material is polished with sandpaper, the sandpaper specification is 2000-8000 mesh; then the polished graphite material is washed with ultrapure water and dried at room temperature. The purity of the graphite material reaches 99.999%. The electrolyte volume is 10-5000mL, and the reaction time is 1-500h under constant potential conditions.
[0014] As an embodiment of the present invention, in step S1, the electrolyte includes one or more of ultrapure water, acid solution, alkaline solution, and salt solution. The pH of ultrapure water, acid solution, and alkaline solution is 1-12, preferably 2-11; and the solubility of the salt solution does not exceed 5 mmol / L.
[0015] The acid solution is one or more of hydrochloric acid solution and acetic acid solution;
[0016] The alkaline solution is one or more of sodium hydroxide solution and ammonia water;
[0017] The salt solution is one or more of sodium chloride solution, potassium chloride solution, sodium bicarbonate solution, magnesium sulfate solution, calcium chloride solution, sodium acetate solution, and sodium carbonate solution.
[0018] As an embodiment of the present invention, in step S1, the voltage of electrolysis is 25-60V.
[0019] As an embodiment of the present invention, in step S1, the distance between electrodes is 6-10 cm, preferably 8 cm.
[0020] As an embodiment of the present invention, in step S1, different electrolyte components are used, and different conductivity during electrolysis can be used to prepare hydrophilic graphite oxide particles of different sizes to achieve size control. For example, when ultrapure water is used as an electrolyte for electrolysis, the smaller the current generated, the smaller the particle size; the larger the current, the larger the particle size (high conductivity, too large current will not act on the surface of the graphite anode and break the CC bond).
[0021] As an embodiment of the present invention, in step S2, filtering is performed by using filter paper (fast, medium, slow) or filter membrane (0.22-0.8 micron). When the purity of the graphite electrode is not high enough, large particles increase significantly, and filtering can filter out large particles of sediment visible to the naked eye.
[0022] As an embodiment of the present invention, in step S2, the size range of the hydrophilic graphite oxide particle material obtained is 3-80nm, preferably 5-50nm. Particles of different sizes are distributed in the electrolysis product. By controlling the electrolysis parameters (voltage or electrolyte), the particles obtained are mainly particles not exceeding 80nm, and there are a small number of large-size particles (80-800nm). The particles in the supernatant in the filtrate are small, and the particles in the lower layer are large. According to the distribution of particle size in the filtrate, multi-step centrifugation is performed to separate hydrophilic graphite oxide particles of different particle sizes. This step can further centrifuge the supernatant or the lower layer. The more separation times, the more uniform the size of the hydrophilic graphite oxide particles in the obtained separated liquid.
[0023] As the particle size increases (80-800nm), the surface defect density decreases, the storage electron density also decreases, and the reduction effect becomes weaker. When the particles reach the micron level, the electron storage content per unit mass of graphite particles is further reduced, and the main effect is adsorption when used (no reduction effect, equivalent to conventional carbon powder and graphene powder).
[0024] As an embodiment of the present invention, in step S2, the centrifugal speed is 1000-15000 rpm, and the centrifugal time is 10-60 min.
[0025] As an embodiment of the present invention, in step S2, the hydrophilic graphite oxide particle material obtained is a hydrophilic graphite oxide particle dispersion obtained by centrifugal separation. The prepared graphite oxide particle material can be highly dispersed in an aqueous solution. The hydrophilic graphite oxide particles serve as electron donors, and the electron-providing capacity is 0.01-0.2 mmol·g -1 The final product is evenly dispersed in the solution and can be highly dispersed in the aqueous solution without further ultrasonic dispersion or the addition of additional dispersants or stabilizers.
[0026] In a second aspect, the present invention provides an application of the hydrophilic graphite oxide particle material in reducing heavy metal ions. The application is an application in environmental remediation. The graphite particle material obtained by the present invention has the characteristics of reducing properties and can be used for heavy metal wastewater treatment, reducing heavy metal ions and recovering them.
[0027] The application includes recovering the heavy metal obtained after reducing the heavy metal ions.
[0028] The metal ions include one or more of dichromate ions, chloroaurate ions, and permanganate ions.
[0029] The heavy metal ions are derived from heavy metal wastewater and / or heavy metal ions in environmental water.
[0030] As an embodiment of the present invention, the application comprises the following steps: adding the hydrophilic graphite oxide particle material into a water body containing heavy metal ions (heavy metal wastewater system or environmental water body), stirring and mixing evenly. The concentration of heavy metal ions is 0.1-1000 mg·L -1 .
[0031] The application in heavy metal wastewater treatment includes the following steps:
[0032] (1) adding the hydrophilic graphite oxide particle material to a heavy metal wastewater system; the concentration of heavy metal ions in the wastewater is 0.1-1000 mg·L -1 ;
[0033] (2) Stir the mixed solution of step (1) evenly.
[0034] By adding hydrophilic graphite oxide particle dispersion into heavy metal wastewater, the heavy metal ion pollutants in the wastewater can be reduced and toxic species can be removed.
[0035] The present invention utilizes electrochemistry as a green and pollution-free method to prepare hydrophilic graphite oxide particle materials, and utilizes a large number of oxygen functional groups contained in the hydrophilic graphite oxide particle materials themselves, such as hydroxyl (-OH), carboxyl (-COOH), epoxy (-O-), etc. These functional groups give them good hydrophilicity and chemical reaction activity, so as to achieve different application capabilities of the hydrophilic graphite oxide particle materials; in addition, based on the controllable and easy operation of the electrochemical method, the size of the hydrophilic graphite oxide particle materials can be controlled by controlling the applied voltage or changing the electrolyte composition.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] (1) The electrochemical oxidation method adopted in the present invention has a simple process, has no special requirements for the synthesis site, and no other secondary pollution is generated during the preparation process.
[0038] (2) The synthesis method of hydrophilic graphite oxide particle material is simple, easy to promote, and has no toxic side effects on the environment.
[0039] (3) The size of hydrophilic graphite oxide particles can be controlled by controlling the electrochemical applied potential, separation method and electrolyte composition.
[0040] (4) The hydrophilic graphite oxide particle material prepared by the present invention has the characteristic of reducing property, and can realize the conversion of high-valent and toxic Cr(VI) in water into non-toxic Cr(III).
[0041] (5) The hydrophilic graphite oxide particle material prepared by the present invention has the characteristic of reducing property, and can reduce the precious metal ions in the water body to a single substance, thereby realizing the recovery process of the precious metal ions in the water body. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0043] Figure 1 TEM image of graphite oxide particles prepared in Example 1;
[0044] Figure 2 TEM image of graphite oxide particles prepared in Example 2;
[0045] Figure 3 TEM image of graphite oxide particles prepared in Example 3;
[0046] Figure 4 This is a diagram showing the effect of dichromate removal in Example 4;
[0047] Figure 5 This is the XPS spectrum of the product Cr 2p in the dichromate removal process in Example 4;
[0048] Figure 6 This is a diagram showing the effect of dichromate removal in Example 5;
[0049] Figure 7 is the XPS spectrum of Au 4f in the reaction product in Example 6;
[0050] Figure 8 This is a diagram showing the effect of dichromate removal in Comparative Example 1;
[0051] Fig. 9 is the XPS spectrum of Au 4f in the reaction product in Comparative Example 2;
[0052] Fig.10 TEM image of the graphene product in Comparative Example 3;
[0053] Fig.11 This is the TEM image of the product prepared in Comparative Example 4. DETAILED DESCRIPTION
[0054] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several changes and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0055] The present invention provides a graphite particle material prepared by an electrochemical oxidation method. The graphite particle material has a high dispersion property in an aqueous solution and good hydrophilicity. In addition, in terms of sewage treatment application, the hydrophilic graphite particle material has a certain reducibility, and its ability to provide electrons as an electron donor is 0.01-0.2mmol·g -1 .
[0056] The graphite particle material is prepared by electrochemical oxidation method using graphite as an electrode to form a two-electrode electrochemical system with an electrolyte such as an aqueous solution. The graphite particle material is then placed in an environmental water body contaminated by heavy metal ions to reduce the toxicity of the water body.
[0057] Example 1
[0058] Preparation of oxidized graphite particles:
[0059] Insert two clean graphite plates (10 cm × 10 cm) into 1500 mL of electrolyte (pH = 4.5, the solvent is water, and the pH is adjusted with hydrochloric acid) to form an electrochemical oxidation method to prepare a hydrophilic graphite oxide material system. Turn on the power and set the input voltage of the electrochemical oxidation method to 45V. After power is turned on, bubbles are generated on the surfaces of the positive and negative graphite plates in the electrochemical oxidation system. After a period of reaction (15h), the color of the electrolyte solution changes from colorless and transparent to light brown and finally to yellowish brown. Use a filter membrane to filter the electrolyte to obtain a bright yellow solution. Centrifuge at 15000 rpm for 45 minutes, remove the lower layer of liquid, and centrifuge at 15000 rpm for 45 minutes again to remove the lower layer of liquid. Hydrophilic graphite particles with a particle size of about 40 nm and a concentration of about 1500 mg·L -1 .
[0060] Figure 1 This is a scanning transmission electron microscope image of oxidized graphite particles. Figure 1 It can be seen that the oxidized graphite particles are uniform in size.
[0061] Example 2
[0062] Preparation of oxidized graphite particles:
[0063] Insert two clean graphite plates (10 cm × 10 cm) into 1500 mL of ultrapure water (pH = 7) electrolyte to form an electrochemical oxidation method to prepare a hydrophilic graphite oxide material system. Turn on the power and set the input voltage of the electrochemical oxidation method to 30V. After power is turned on, bubbles are generated on the surface of the positive and negative graphite plates in the electrochemical oxidation system. After a period of reaction (20 hours), the color of the electrolyte solution changes from colorless and transparent to light brown and finally to yellowish brown. Use a filter membrane to filter the electrolyte to obtain a bright yellow solution. Centrifuge at 15000 rpm for 45 minutes and take the upper liquid; centrifuge at 15000 rpm for 45 minutes again and take the upper liquid to obtain hydrophilic graphite particles with a uniform particle size of about 5 nm and a concentration of about 600 mg·L -1 .
[0064] Figure 2 This is a scanning transmission electron microscope image of oxidized graphite particles. Figure 2 It can be seen that the oxidized graphite particles are uniform in size and highly dispersed without agglomeration.
[0065] Dichromate removal effect test
[0066] Evaluation of the reduction effect of chromate ions in sewage: The hydrophilic graphite particle material in Example 2 was added to the chromate ion aqueous solution, stirred evenly, and the reaction began. The chromate ion in the solution was determined by the diphenylcarbohydrazide spectrophotometric method in accordance with the national standard GB 7467-87. The specific operation was as follows: after the reaction started, 1 mL of the reaction solution was taken into a 10 mL colorimetric tube, diluted to 10 mL, and 0.6 mL of deionized water was added as a blank sample for a group of experiments. At each determined sampling time point, 1 mL of the reaction solution was taken into a 10 mL colorimetric tube, diluted to 10 mL, and then 100 μL of 1:1 phosphoric acid solution and 100 μL of 1:1 sulfuric acid solution were added. Finally, 400 μL of color developer (0.2 g of diphenylcarbohydrazide was dissolved in 50 mL of acetone solution and diluted to 100 mL with water) was added. After shaking evenly, it was transferred into a 10 mm colorimetric dish. The absorbance after deducting the blank was detected using an ultraviolet spectrophotometer, and the maximum absorption value at 540 nm was taken. Combined with the standard curve prepared in advance, the concentration of chromate ions in the solution was calculated. The initial concentration of chromate ions was 2.5-10 mg L -1 The concentration of hydrophilic graphite particles is 300 mg·L -1 , the reaction volume was 50 mL, and the initial reaction pH was 3.0.
[0067] Figure 4 The figure shows the reduction effect of hydrophilic graphite particles with different concentrations mixed with chromate solution. Figure 4It can be seen that the amount of chromium ions reduced per unit time is positively correlated with the mass concentration of graphite particle material, and the unit mass (per gram) of graphite particle material can provide 0.07-0.10 mmol of electrons. Figure 5 The XPS test results of the black powder obtained by freeze-drying the mixture of graphite particles and chromate solution show that hydrophilic graphite particles can reduce dichromate to Cr(III).
[0068] Test on the recovery effect of precious metal ions in water
[0069] Evaluation of the recovery effect of precious metal ions in water: The hydrophilic graphite particles in Example 2 were placed in an aqueous solution of chloroaurate ions, stirred evenly, and the reaction began. The mass concentration of the precious metal Au(III) was 500 mg·L -1 , the mass concentration of graphite particles is 1000 mg·L -1 , the reaction volume is 25 mL, pH = 3.0. After the graphite particles are mixed with chloroauric acid for 48 hours, the mixed solution is freeze-dried to obtain a dry black powder.
[0070] Figure 7 This is a graph of the test results of X-ray photoelectron spectroscopy (XPS) technology on the freeze-dried sample. From the test results, it can be seen that the XPS test only detects the signal peak of Au element. After the graphite particle material reacts with chloroauric acid, chloroauric acid can be reduced to elemental gold.
[0071] Example 3
[0072] Preparation of oxidized graphite particles:
[0073] Two clean graphite plates (10 cm × 10 cm) were inserted into 1500 mL of simulated groundwater (KCl = 1 mmol·L -1 , NaHCO3=2mmol·L -1 , MgSO4=0.5mmol·L -1 , CaCl2=0.5mmol·L -1 ) in the electrolyte, forming an electrochemical oxidation method for preparing a hydrophilic graphite oxide material system. Turn on the power and set the input voltage of the electrochemical oxidation method to 30V. After power is turned on, bubbles are generated on the surface of the positive and negative graphite plate electrodes in the electrochemical oxidation system. After a period of reaction (10h), the color of the electrolyte solution changes from colorless and transparent to light brown and finally to yellowish brown. The electrolyte is filtered using a filter membrane to obtain a bright yellow solution. After high-speed centrifugation at 15000rpm for 45min, the upper layer of liquid is taken to obtain hydrophilic graphite particles with a particle size of about 10nm ( Figure 3 ).
[0074] Evaluation of chromate ion reduction effect in sewage:
[0075] The hydrophilic graphite particles in Example 3 were added to the chromate ion aqueous solution, stirred evenly, and the reaction was started. The chromate ions in the solution were determined according to the diphenylcarbazide spectrophotometric method of the national standard GB 7467-87, and the specific operation was the same as that in Example 4. The initial concentration of chromate ions was 2.5 mg·L -1 , the concentration of hydrophilic graphite particles is 1000-3000 mg·L -1 , the reaction volume was 50 mL, and the initial reaction pH was 3.0.
[0076] Figure 6 The figure is the result of the reduction effect of chromate solution. Figure 6 It can be seen that the graphite particle material has reducing properties, and the amount of chromium ions reduced per unit time is positively correlated with the mass concentration of the graphite particle material.
[0077] Comparative Example 1
[0078] Evaluation of the reduction effect of chromate ions in wastewater: Commercial graphite powder was used to replace the hydrophilic graphite particle material in Application Example 1, and other experimental conditions were consistent with Application Example 1. Figure 8 It can be seen that as the reaction time progresses, the concentration of chromate ions in the solution hardly changes, indicating that commercial graphite powder does not have the ability to reduce chromate ions.
[0079] Comparative Example 2
[0080] The hydrophilic graphite particle material in Application Example 2 was replaced with commercial graphite powder material, and other experimental conditions were consistent with those in Example 6. Fig. 9 This is the XPS test result diagram after mixing. From the test results, it can be seen that the XPS test only detects the signal peak of Au(III), indicating that after the graphite powder material is mixed with chloroauric acid, chloroauric acid cannot be reduced to elemental gold.
[0081] Embodiment 4-7
[0082] The preparation method is basically the same as that of Example 1, except that the parameters such as the electrolyte and its concentration, voltage, etc. are as shown in Table 1.
[0083] Comparative Examples 3-4
[0084] The preparation method is basically the same as that of Example 1, except that the parameters such as the electrode solution and its concentration, voltage, etc. are as shown in Table 1.
[0085] Table 1
[0086]
[0087]
[0088] The oxidized graphite particles obtained in Examples 1, 4, and 5 were measured by dynamic light scattering to have a particle size of approximately 40 nm. The results of Examples 3, 6, and 7 show that the larger the applied voltage, the larger the system current, and the larger the particle size of the oxidized graphite particles separated. In Comparative Example 3, the electrolyte was replaced with 0.2 mol·L -1 The other operation methods are the same as those in Example 3, such as Fig.10 As shown, the obtained product is an ultra-thin graphene film. In Comparative Example 4, the voltage is too small, and the product is in the form of a graphene film ( Fig.11 ).
[0089] The present invention discloses an electrochemical oxidation method for preparing hydrophilic graphite oxide granules of different sizes and their application, wherein graphite material electrodes are used as positive and negative electrodes respectively, and a constant potential method is used to prepare the graphite oxide granules. The prepared graphite oxide granules have a high degree of hydrophilicity and can also be used to repair environmental wastewater, such as heavy metal ion reduction.
[0090] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various changes or modifications within the scope of the claims, which does not affect the essence of the present invention. In the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other arbitrarily.
Claims
1. An application of a hydrophilic graphite oxide particle material in reducing heavy metal ions, characterized in that: The hydrophilic graphite oxide particle material is prepared by the following method: S1. Select graphite as the anode, insert the anode and cathode into the electrolyte, and perform electrolysis at a constant potential; S2. After the electrolysis is completed, the obtained electrolytic solution is filtered, and the filtrate is centrifuged to obtain the hydrophilic graphite oxide particle material; In step S1, the electrolyte includes one or more of ultrapure water, acid solution, alkaline solution, and salt solution; the pH of the ultrapure water, acid solution, and alkaline solution is 1-12; and the solubility of the salt solution does not exceed 5 mmol / L; In step S1, the voltage of electrolysis is 25-60V.
2. The use according to claim 1, characterized in that: The heavy metal ions include one or more of dichromate ions, chloroaurate ions, and permanganate ions.
3. The use according to claim 1, characterized in that: The application comprises the following steps: adding the hydrophilic graphite oxide particle material into a water body containing heavy metal ions, and stirring and mixing evenly.
4. The use according to claim 1, characterized in that: The acid solution is one or more of a hydrochloric acid solution and an acetic acid solution.
5. The use according to claim 1, characterized in that: The alkaline solution is one or more of sodium hydroxide solution and ammonia water.
6. The use according to claim 1, characterized in that: The salt solution is one or more of sodium chloride solution, potassium chloride solution, sodium bicarbonate solution, magnesium sulfate solution, calcium chloride solution, sodium acetate solution, and sodium carbonate solution.
7. The use according to claim 1, characterized in that: In step S1, the distance between electrodes is 6-10 cm.
8. The use according to claim 1, characterized in that: In step S2, the size range of the obtained hydrophilic graphite oxide particle material is 3-80 nm.
9. The use according to claim 1, characterized in that: In step S2, the centrifugal speed is 1000-15000 rpm, and the centrifugal time is 10-60 min.
10. A hydrophilic graphite oxide particle material prepared by an electrochemical method, characterized in that: Prepared by the following method: S1. Select graphite as the anode, insert the anode and cathode into the electrolyte, and perform electrolysis at a constant potential; S2. After the electrolysis is completed, the obtained electrolytic solution is filtered, and the filtrate is centrifuged to obtain the hydrophilic graphite oxide particle material; In step S1, the electrolyte includes one or more of ultrapure water, acid solution, alkaline solution, and salt solution; the pH of the ultrapure water, acid solution, and alkaline solution is 1-12; and the solubility of the salt solution does not exceed 5 mmol / L; In step S1, the voltage of electrolysis is 25-60V.
Citation Information
Patent Citations
Method for preparing nano oxidized graphite particle or flake graphite and benzene hexacarbonic acid simultaneously
CN101469431A
Ultra-small oxidized graphene-gold nano particle immune complex and preparation method thereof
CN104922666A
Method for preparing water soluble graphene
CN107235486A
Graphene quantum dot and application thereof
CN111318279A
Method for Continuously Preparing Graphene Oxide Nanoplatelet
US20190112195A1